Transpiration and moisture evolution in packaged fresh horticultural produce and the role of integrated mathematical models: A review. (October 2016) - Bovi, Graziele G.; Caleb, Oluwafemi J.; Linke, Manfred; Rauh, Cornelia; Mahajan, Pramod V.
Abstract : Transpiration has various adverse effects on postharvest quality and the shelf-life of fresh fruit and vegetables (FFV). If not controlled, the water released through this process results in direct mass loss and moisture condensation inside packaged FFV. Condensation represents a threat to the product quality as water may accumulate on the product surface and/or packaging system, causing defects in external appearance and promoting growth of spoilage microorganisms. Thus, moisture regulation is extremely important for extending FFV shelf-life. This review focuses on transpiration phenomenon and moisture evolution in packaged fresh horticultural produce. It provides recent information on various moisture control strategies suitable for packaging of fresh horticultural produce. It also provides an evaluation on the role and application of integrative mathematical modelling in describing water relations of FFV for packaging design, as well as, an overview of models reported in literature. Highlights: Fresh produce continues to give off moisture even under saturated conditions. Respiration and transpiration both plays an important role in moisture evolution. Moisture condensation on product surface promotes growth of spoilage microorganisms. Humidity-regulating tray offers a novel approach for moisture control. Integrative mathematical model presents possible solution for package optimisation.